Geostatistics applied in soil compaction determination in sugar cane cropping - Marasca, Indiamara; Gladenucci, Joanina [UNESP]; Spadim, Emanuel Rangel [UNESP]; Barbosa, Rodrigo Domingues [UNESP]; Lancas, Kleber Pereira [UNESP] (Univ Estadual Mato Grosso Sul, 2017)
The tools of precision agriculture increasingly diversify to facilitate decision making in the field in order to increase crop yields to feed a population that only grows. The responsibility of professional in agronomic areas must be grounded in the study and mastery of new technologies. The objective of this work was to demonstrate the technique of data interpolation to make soil maps using Gamma Desing software and the study of geostatistics. The soil penetration resistance was obtained to a depth of 0.45 m. Gamma Desing software was used for the transepts maps preparation for treatments. Data showed that the layer from 0.30 to 0.45 m in conventional tillage was the only one which showed no spatial dependence. The use of geostatistics as a tool in agriculture had satisfactory response and the Gamma Desing program was reliable in maps interpolation for the soil compaction variable.
Keywords: Cone index; spatial variability; deep preparation